Improvement of wind turbine lightning receptor - Mohammed Ahmed Al-Fakih, Nawfan Mohammed (2021)
Lightning receptor is a device attached to a wind turbine blade that will attract and assist lightning current flow to the ground. However, lightning does not necessarily strike it, instead the other part of the wind turbine is still been stroked by lightning eventually leading to catastrophe damage of the wind turbine. This research is aimed to develop a needle-type receptor on a wind turbine blade for lightning protection system (LPS). Other than that, this project is aimed to study the practical parameters of lightning protection system, including the relation between receptor size and electric field strength. The receptors were designed by three different disk diameters of 0.2 m, 0.5 m and 0.8 m. In 0.2m receptor diameter, the comparison between the numbers and length of needles presents that 32 number of needles and 0.3m length of needles can attract a higher electrical field than others. Each disk diameter consists of different needles number and length. Finite Element Method (FEM) has used for this research, the proper dimensions and shapes of receptors simulated by suggesting the minimum and maximum electric field that accumulates around receptors. The simulation study plays an active role in understanding and designing the receptor of wind turbines for an effective lightning protection system (LPS), but it requires a validation under actual conditions